Tourism Activity Sustainable Tourism for Community Development in Khlong Mon, Lat Krabang - อ้นยะ ภณสิทธ์; กลั่นมา กวีกานต์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The research titled Tourism Activity Models for Community Development in Khlong Mon, Lat Krabang Towards Sustainable Tourism aims to explore appropriate tourism activity development strategies for the Klong Mon community, based on the concept of Community-Based Tourism (CBT). The study employs both qualitative and quantitative research methods, including in-depth interviews with community leaders, tourists, and relevant organizations, as well as an assessment of the area’s tourism potential. The findings indicate that Klong Mon possesses strengths in its natural resources, cultural heritage, and unique local way of life. However, limitations remain in terms of infrastructure, tourism management, and community participation. The research suggests four key development strategies: (1) promoting cultural and eco-tourism activities, (2) improving tourism-related facilities and infrastructure, (3) fostering collaboration between the community and various stakeholders, and (4) enhancing the capacity of local residents to effectively manage tourism in a sustainable manner.